PENGARUH KEMASAN DAN DAYA TARIK IKLAN TERHADAP CITRA MEREK SERTA PREFERENSI MEREK DI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Mahasiswa/i Undip Konsumen AQUA) - Maslakhah, Ida; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2017)
This study is aims to analyze the influence of packaging and advertising appeal on brand image and brand preference in social media to purchase decisions (study on students Undip consumer AQUA).The data collecting method is done through a questionnaire with close and open questions to 100 respondents. Sampel criteria such as students of Undip, who watch advertising of AQUA in mass media or social media and buying AQUA in 2016/2017. Multiple regression analysis in SPSS program is used for this study. The results showed that the packaging and advertising appeal has positive and significant effect on brand image, and then brand image and brand preference in social media has positive and significant effect on purchase decisions.